(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: At present, the health service system is under pressure to reduce costs. This situation is associated with risks for the health of the employees themselves, as well as for the quality of treatment and care. The aim of the study was to investigate stressors and resources which are present in the interactions of employees with patients at an orthopaedic clinic of a Swiss cantonal hospital and to analyse their relationship to the health of employees and their patient orientation. METHODS: A questionnaire was administered to 162 employees of different occupational groups at the clinic (including physicians, nurses and secretaries). In order to investigate the relationships between working conditions, employee health and the patient orientation of employees, correlations were calculated and regression analyses were conducted. RESULTS: The results of the study demonstrate that working conditions in the interaction with patients indeed predict health problems, as well as quality of health services provided. Especially stressors in the form of barriers to patient-oriented work are significant predictors of emotional exhaustion, aversion to patients, physical complaints and a (lower) patient orientation of employees. CONCLUSIONS: The results of the investigation of the clinic in question led to the formation of health circles, including the participation of different occupational groups, and to the introduction of measures for reducing stressors in the interaction with patients.